Konsep Modernisasi dan Implikasinya terhadap Penelitian dan Pengembangan Pertanian - Tri Pranadji; Pantjar Simatupang (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1999)
EnglishAs a respons to meet globalization challenges in the 21st century, agricultural modernization is considered as agribusiness adjustment process to the latest development of science and technology. In other words, agricultural modernization can be seen as ''cathing-up